Utilization of dental services by rural riverside populations covered by a Fluvial Family Health Team in Brazil - Diego Cordeiro; Fernando Herkrath; Adrielly Guedes; Luiza Garnelo; Ana Paula Herkrath (James Cook University, 2024)
Introduction: Rural riverside populations of Brazil face several difficulties to access health services. The Brazilian National Primary Care Policy implemented the Fluvial Family Health Teams (FFHT), which is a specific primary care team arrangement for these territories. The aim of the study was to assess the use of dental services by adults living in rural riverside areas covered by a FFHT. Methods: A household-based cross-sectional survey was carried out with a rural riverside population of 38 localities on the left bank of the Rio Negro, Manaus, Amazonas, representative of the area covered by the FFHT. Stratified random sampling was calculated based on the number of adults and households in each riverside locality. An electronic questionnaire was used to obtain information on sociodemographic and oral health conditions, and the utilization of dental services. After descriptive analysis, logistic regression analyses were performed to estimate the odds ratios for the outcome 'use of dental health services over the past 12 months'. Results: A total of 492 individuals, aged 18 years or more, from 38 rural riverside areas were assessed. The mean age of participants was 43.5 years (standard deviation 17.0), ranging from 18.0 to 90.7 years. Of these participants, 3.1% had never been to a dentist and 21.9% had been to a dentist more than 3 years ago. Among those who attended the dental service, 77.4% of appointments occurred in public health services. Dental pain over the previous 6 months (odds ratio (OR)=2.44; 95% confidence interval (CI) 1.51-3.96), higher education (OR=2.62; 95%CI 1.23-5.56), most recent appointment in public health services (OR=1.86; 95%CI 1.19-2.93), edentulism (OR=0.38; 95%CI 0.17-0.85) and dissatisfaction with oral health (OR=0.59; 95%CI 0.38-0.93) were associated with the dental services utilization. Conclusion: The study results revealed that approximately a quarter of the individuals did not use dental services over the previous 3 years or have never used them. Despite the increase in access provided by the FFHT, edentulous individuals, individuals dissatisfied with their oral health, and those with lower levels of education were less likely to use dental services, while individuals who experienced dental pain sought dental services more frequently. These findings suggest that the healthcare model offered to this population must be rearranged.